2013
DOI: 10.1186/1471-2180-13-241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spaceflight on Pseudomonas aeruginosa final cell density is modulated by nutrient and oxygen availability

Abstract: BackgroundAbundant populations of bacteria have been observed on Mir and the International Space Station. While some experiments have shown that bacteria cultured during spaceflight exhibit a range of potentially troublesome characteristics, including increases in growth, antibiotic resistance and virulence, other studies have shown minimal differences when cells were cultured during spaceflight or on Earth. Although the final cell density of bacteria grown during spaceflight has been reported for several spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 43 publications
(86 reference statements)
1
52
0
Order By: Relevance
“…Ref. [55] also reported an increase in final cell count in space and that the difference between spaceflight and Earth controls could be minimized by the addition of growth-limiting substrates. Collectively, the enhanced growth condition explanation suggested to occur as a result of the proposed altered environmental factors in microgravity is further supported by the new gene expression data.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. [55] also reported an increase in final cell count in space and that the difference between spaceflight and Earth controls could be minimized by the addition of growth-limiting substrates. Collectively, the enhanced growth condition explanation suggested to occur as a result of the proposed altered environmental factors in microgravity is further supported by the new gene expression data.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some microbial isolates were collected from astronauts and filter debris during orbital spaceflights on the International Space Station (ISS) (Checinska et al, 2015;Venkateswaran et al, 2014). It has been reported that the space environment can alter the microbial growth rate, virulence, and antibiotic susceptibility (Kim et al, 2013;Klaus & Howard, 2006;Mora et al, 2016;Rosenzweig, Ahmed, Eunson, & Chopra, 2014;Taylor, 2015;Urbaniak et al, 2018;Wilson et al, 2007). In addition, many studies have shown that the extreme environment of space plays an important role in dysregulation of the human immune system (Crucian et al, 2018;Kaur, Simons, Castro, Ott, & Pierson, 2005;Taylor, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, space microgravity produced thicker bioflims that exhibited motility-dependent, aberrant architectures (column and canopy structure) relative to the ground control cultures (Kim et al 2013a). Interestingly, when phosphate and oxygen levels were reduced, P. aeruginosa exhibited increased final biomass/enhanced growth during spaceflight (Kim et al 2013b). Whereas the contents of M9 salts diminished salmonellae hypervirulence in murine infections following spaceflight and phosphate was speculated to be the key factor (Wilson et al 2008), phosphate also positively influenced P. aeruginosa growth during spaceflight (Kim et al 2013b).…”
Section: Spaceflight Experiments and Their Inherent Limitationsmentioning
confidence: 99%
“…Interestingly, when phosphate and oxygen levels were reduced, P. aeruginosa exhibited increased final biomass/enhanced growth during spaceflight (Kim et al 2013b). Whereas the contents of M9 salts diminished salmonellae hypervirulence in murine infections following spaceflight and phosphate was speculated to be the key factor (Wilson et al 2008), phosphate also positively influenced P. aeruginosa growth during spaceflight (Kim et al 2013b). It seems that some spaceflight responses of various bacteria seem dependent on specific nutritional factors (e.g., the presence of phosphate).…”
Section: Spaceflight Experiments and Their Inherent Limitationsmentioning
confidence: 99%